2014
DOI: 10.1002/hfm.20587
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Coworker Incivility, Emotional Exhaustion, and Organizational Outcomes: The Mediating Role of Emotional Exhaustion

Abstract: The aim of this research is to investigate the relationship between coworker incivility, emotional exhaustion, and organizational outcomes measured by job satisfaction, job performance, and turnover intention. Working with a sample of 286 retail bank employees in South Korea, structural equation modeling is employed to test four hypotheses drawing on conservation of resources (COR) theory and affective events theory (AET). According to the analyses, while employee incivility positively affects emotional exhaus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
87
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(94 citation statements)
references
References 69 publications
3
87
1
3
Order By: Relevance
“…The turnover intention was measured using a scale developed by Netemeyer and Brashear et al (Hur, Kim, & Park, 2015). Responses range in 5 range scale, from 1 (strongly disagree) to 5 (strongly agree).…”
Section: Turnover Intention (Ti)mentioning
confidence: 99%
“…The turnover intention was measured using a scale developed by Netemeyer and Brashear et al (Hur, Kim, & Park, 2015). Responses range in 5 range scale, from 1 (strongly disagree) to 5 (strongly agree).…”
Section: Turnover Intention (Ti)mentioning
confidence: 99%
“…From an empirical point of view, exhaustion has been found to be critical in understanding the psychological experience associated with incivility (Hur et al, 2015). A recent study by Fida et al (2017) provided evidence for the predicting role of incivility on exhaustion at a distance of one year.…”
Section: The Association Between Co-worker Incivility and Exhaustionmentioning
confidence: 99%
“…According to this corpus of literature, experiencing co-worker incivility leads to increased exhaustion (Fida, Laschinger, & Leiter, 2017; Hur, Kim, & Park, 2015) and turnover intent, as well as deteriorated job satisfaction (Lim, Cortina, & Magley, 2008) and commitment (Taylor, Bedeian, & Kluemper, 2012). Several studies demonstrated that incivility also has the potential to spiral into increasingly deviant behaviours that may undermine the social climate in the organisation.…”
mentioning
confidence: 99%
“…In this section, a series of questions regarding teachers' freedom of expressing their personal and group problems to the principal, their active participation in decision-making and educational planning, the principal welcome when teachers give constructive criticism, the principal's efforts to create friendly relationships among teachers and giving importance to new strategies at school affairs were posed (19)(20)(21)(22).…”
Section: Participative Management Promotionmentioning
confidence: 99%